Three new micro-endemic species of Paepalanthus (Paepalanthoideae, Eriocaulaceae) from Serra do Ambrósio, Minas Gerais, Brazil - Costa, Fabiane Nepomuceno; Andrino, Caroline Oliveira; Trovó, Marcelo; Echternacht, Livia; Sano, Paulo Takeo (Phytotaxa, 2016)
We describe and illustrate three new species of Paepalanthus (Eriocaulaceae: Paepalanthoideae) from the Espinhaço Range: P. argyrotrychus, P. farinaceus and P. velutiphyllus, all endemic to Serra do Ambrósio, a mountain disjunct from the Espinhaço Range in the municipality of Rio Vermelho, Minas Gerais, Brazil. These species belong to Paepalanthus ser. Paepalanthus (=Paepalanthus [unranked] Variabiles). We provide detailed descriptions and illustrations for each taxon, as well as comments on habitat, distribution, morphology, conservation and their affinities to the most morphologically similar species.